Implementation of Piano Teaching Methods in the Professional Training of Vocal Students - Liashenko, Olga; Harkusha, Liudmyla (Educological discourse, 2025)
The article scientifically substantiates the role of the piano in the professional training of vocal students at the university and proves the appropriateness of applying pianistic methods and techniques in vocal education practice. The scientific and educational-methodological literature on the professional training of university students in piano and vocal classes has been analyzed. Less-researched aspects of this scientific problem have been identified, and tasks for their theoretical justification and practical implementation in the educational process have been outlined. The methods of scientific research, the application of which ensures a comprehensive exploration of the chosen topic, have been determined. The specifics of teaching vocalists in the piano class have been revealed. The basic principles of teaching piano in the university education system have been analyzed. The theoretical and practical aspects of students’ educational activities in the piano class have been characterized. A comparison of the tasks of piano training for instrumental students and vocal students has been made. The professional functions of a music instrument teacher at the university (educational, developmental, educational, artistic-creative, and scientific-methodological) have been outlined. The necessity of familiarizing piano instructors with the content of vocal training for students has been proven, with the aim of identifying those types of educational work that require the application of pianistic skills and specific playing techniques. Aspects that teachers should consider to motivate vocal students and professionally guide their piano training have been identified. The necessity of interdisciplinary interaction in shaping the professional competencies of vocal students in the piano class has been argued. Examples of the application of pianistic skills in performing vocal exercises on the piano, which require knowledge from music-theoretical disciplines, have been provided. The methods of piano training for students specializing in "Solo Singing" have been structured, and their pedagogical purpose has been defined. It has been stated that the piano classes for vocal students ensure the implementation of pianistic skills and techniques in the practice of vocal training.